Gallic acid alleviates gastric precancerous lesions through inhibition of epithelial mesenchymal transition via Wnt/β-catenin signaling pathway. (10th February 2023) - Liao, Wenhao; Wen, Yueqiang; Wang, Jing; Zhao, Maoyuan; lv, Shangbin; Chen, Nianzhi; Li, Yuchen; Wan, Lina; Zheng, Qiao; Mou, Yu; Zhao, Ziyi; Tang, Jianyuan; et al.
Abstract: Ethnopharmacological relevance: Gallic acid (GA) is a natural polyphenolic compound derived from Rhus chinensis Mill. with a variety of biological activities such as astringent sweat, cough, dysentery, hemostasis, and detoxification, and is widely used in China as a treatment for cough, bleeding, and gastrointestinal disorders. In recent years, the anticancer activity of GA has been demonstrated in a variety of cancers, affecting multiple cellular pathways associated with cancer onset, development and progression. Aim of the study: To investigate the role and potential mechanism of GA on gastric precancerous lesions (GPL), the key turning point of gastritis to gastric cancer, with the aim of delaying, blocking or reversing the dynamic overall process of "inflammation-cancer transformation" and thus blocking GPL to prevent the development of gastric cancer. Materials and methods: In this study, we established N-Nitroso-N-methylurea (MNU)-induced GPL mice model and induced precancerous lesions of gastric cancer cells (MC), i.e. epithelial mesenchymal transition (EMT), in human gastric mucosal epithelial cells (GES-1) with N-methyl-N′-nitro-N-nitrosoguanidine (MNNG). We used conventional pathology, immunohistochemistry, RNA sequencing, Western blot and other techniques to study the therapeutic effect of GA on GPL and its possiblemechanism in vitro and in vivo. Results: The results showed that compared with normal GES-1 cells, MC cells had the characteristics of malignant cells such as abnormal proliferation, invasion and metastasis, accompanied by decreased expression of EMT-related protein E-cadherin and increased expression of N-cadherin and Vimentin. GA can inhibit the malignant behavior of MC cell proliferation and induce its G0/G1 phase arrest, which is achieved by downregulating the Wnt/β-catenin signaling pathway and thereby inhibiting the EMT process. However, when we incubated with the Wnt pathway activator (Wnt agonist 1), the effect of GA was reversed. Furthermore, analysis of human gastric specimens showed that activation of the Wnt/β-catenin pathway was significantly associated with GPL pathological changes. Meanwhile, GA reversed MNU-induced intestinal metaplasia and partial dysplasia in GPL mice. Conclusion: Taken together, these results indicate that GA prevents the occurrence and development of GPL by inhibiting the Wnt/β-catenin signaling pathway and then inhibiting the EMT process, which may become potential candidates for the treatment of GPL. Graphical abstract: Image 1